Determining fair rental value of land in the Hungarian valuation practice – a methodological approach - Buzás, Ferenc; Kiss, Sándor; Mező, István (Applied Studies in Agribusiness and Commerce, 2020)
The directive of 1666/2015. (IX. 21.) called ’Land for Farmers!’ has changed not only the legal terms and conditions but also the economic basis of land use in the relation of land use and resulting derivative demand. Institutionalized rental fees can be modified to market level only if it is confirmed by qualified expert’s report hired by the new land owner. Setting a fair rental value has quite a few methodological approaches. Due to the lack of a legally recommended calculation process, authors hereby are presenting a method to calculate fair rental value that is beneficial for both renter and owner. Foreign rental conditions related to the topic are also concerned in the article.